Methane yield and species diversity dynamics of perennial wild plant mixtures established alone, under cover crop maize (Zea mays L.), and after spring barley (Hordeum vulgare L.). Issue 11 (14th August 2019) - von Cossel, Moritz; Steberl, Kathrin; Hartung, Jens; Pereira, Lorena A.; Kiesel, Andreas; Lewandowski, Iris
Abstract: The cultivation of perennial wild plant mixtures (WPMs) in biogas cropping systems dominated by maize ( Zea mays L.) restores numerous ecosystem functions and improves both spatial and temporal agrobiodiversity. In addition, the colorful appearance of WPM can help enhance landscape beauty. However, their methane yield per hectare (MYH) varies greatly and amounts to only about 50% that of maize. This study aimed at decreasing MYH variability and increasing accumulated MYH of WPM by optimizing the establishment method. A field trial was established in southwest Germany in 2014, and is still running. It tested the effects of three WPM establishment procedures (E1: alone [without maize, in May], E2: undersown in cover crop maize [in May], E3: WPM sown after whole‐crop harvest of spring barley [ Hordeum vulgare L.] in June) on both MYH and species diversity of two WPMs [S1, S2]). Mono‐cropped maize and cup plant ( Silphium perfoliatum L.) were used as reference crops. Of the WPM treatments tested, S2E2 achieved the highest (19, 296 m N 3 / ha, 60.5% of maize) and S1E1 the lowest accumulated MYH (8, 156 m N 3 / ha, 25.6% of maize) in the years 2014–2018. Cup plant yielded slightly higher than S2E2 (19, 968 m N 3 / ha, 62.6% of maize). In 2014, the WPM sown under maize did not significantly affect the cover crop performance. From 2015 onward, E1 and E2 had comparable average annual MYH and average annual number of WPM species. With a similar accumulated MYH but significantly higher number of species (3.5–10.2), WPM S2E2 outperformed cup plant. Overall, the long‐term MYH performance of WPM cultivation for biogas production can be significantly improved by undersowing with maize as cover crop. This improved establishment method could help facilitate the implementation of WPM cultivation for biogas production and thus reduce the trade‐off between bioenergy and biodiversity. Abstract : The cultivation of perennial wild plant mixtures (WPMs) as biogas substrate combines the production of biomass with the provision of ecosystem services. However, the methane yield per hectare (MYH) is low compared to other biogas crops such as maize and cup plant. In this study, a 5 year field trial investigated the effect of different WPM establishment procedures on the long‐term MYH. While the establishment after spring barley failed, the establishment under maize (a) significantly increased the long‐term MYH of WPM, (b) reduced the risk of establishment failures, and (c) maintained the species diversity from the second year onward.